Shifts in flow and salinity shape phytoplankton communities in the Coorong, a Ramsar-listed shallow coastal lagoon (South Australia) - Daniel Chilton; Justin Brookes; Matthew Hipsey; Tamar Jamieson; Christopher Keneally; Michelle Waycott; Sophie C. Leterme (Continental Shelf Research, 2026)

Phylogenomic analyses of the Austral podocarps (Podocarpus: Podocarpaceae) support hybrid ancestry of a New Zealand species - Raees Khan; Ed Biffin; John Conran; Robert Hill; Kor-jent van Dijk; Michelle Waycott (Molecular Phylogenetics and Evolution, 2026)

Incorporating ecosystem service assessments into development planning − impact from a dredging project in South Australia on seagrass - Sam Gaylard; Rachel Colella; Matt Nelson; Paul Lavery; Michelle Waycott (Ecosystem Services, 2025)

Contribution of seagrass productivity to waste treatment in a highly oligotrophic urbanised coast - Sam Gaylard; Stefan Gabrynowicz; Paul Lavery; Michelle Waycott (Ecosystem Services, 2023)

Population decline in a Pleistocene refugium: Stepwise, drought-related dieback of a South Australian eucalypt - Gunnar Keppel; Udo Sarnow; Ed Biffin; Stefan Peters; Donna Fitzgerald; Evan Boutsalis; Michelle Waycott; Greg R. Guerin (Science of The Total Environment, 2023)

The Risk of Multiple Anthropogenic and Climate Change Threats Must Be Considered for Continental Scale Conservation and Management of Seagrass Habitat - Kathryn McMahon; Kieryn Kilminster; Robert Canto; Chris Roelfsema; Mitchell Lyons; Gary A. Kendrick; Michelle Waycott; James Udy (Frontiers in Marine Science, 2022)
Globally marine-terrestrial interfaces are highly impacted due to a range of human pressures. Seagrass habitats exist in the shallow marine waters of this interface, have significant values and are impacted by a range of pressures. Cumulative risk analysis is widely used to identify risk from multiple threats and assist in prioritizing management actions. This study conducted a cumulative risk analysis of seagrass habitat associated with the Australian continent to support management actions. We developed a spatially explicit risk model based on a database of threats to coastal aquatic habitat in Australia, spanning 35,000 km of coastline. Risk hotspots were identified using the model and reducing the risk of nutrient and sediment pollution for seagrass habitat was assessed. Incorporating future threats greatly altered the spatial-distribution of risk. High risk from multiple current threats was identified throughout all bioregions, but high risk from climate change alone manifested in only two. Improving management of nutrient and sediment loads, a common approach to conserve seagrass habitat did reduce risk, but only in temperate regions, highlighting the danger of focusing management on a single strategy. Monitoring, management and conservation actions from a national and regional perspective can be guided by these outputs.

Genomics-Based Phylogenetic and Population Genetic Analysis of Global Samples Confirms Halophila johnsonii Eiseman as Halophila ovalis (R.Br.) Hook.f. - Michelle Waycott; Kor-jent van Dijk; Ainsley Calladine; Eric Bricker; Ed Biffin (Frontiers in Marine Science, 2021)
Halophila johnsonii is an endangered seagrass species that is restricted to the southeast coast of Florida, United States. Its taxonomic status has been called into question, in particular, given the close morphological and genetic similarity of H. johnsonii and the widely distributed and morphologically variable Halophila ovalis , which is largely restricted to the Indo-Pacific region. While a close relationship to H. ovalis is uncontroversial, it remains uncertain whether H. johnsonii represents a distinct lineage or is a recent introduction to the Florida region. Given the conservation status of H. johnsonii , distinguishing these alternatives has important implications for the management of the species and its habitat. Here, we develop molecular data sets for samples of H. johnsonii and H. ovalis including DNA sequences, genome-wide SNPs and microsatellites with the view to resolving the affinities of H. johnsonii with respect to the wider H. ovalis complex. Phylogenetic hypotheses based upon plastid (∼18000 bp) and low copy nuclear DNA (∼6500 bp) sequences derived from hybrid capture, along with 990 genome-wide ddRAD SNPs consistently resolved H. johnsonii within H. ovalis. Specifically, we found a close affinity between H. johnsonii and H. ovalis sampled from the east coast of Africa. In addition, Halophila specimens collected in Antigua, which are within the range of morphological variation typical for H. ovalis , are virtually identical to H. johnsonii and the East African H. ovalis samples based upon DNA sequence analyses and these group together using Bayesian clustering analyses of microsatellites and ddRAD SNPs. We conducted population genetic analyses using large number of H. johnsonii samples collected over a 17-year period. Genotypic data generated through microsatellites and ddRAD SNPs revealed genetic uniformity for all 132 H. johnsonii samples across the Indian River Lagoon, Florida, while samples of H. ovalis from Antigua shared the same genotype as H. johnsonii . We conclude that the lack of genetic diversity and the absence of sexual reproduction strongly indicates that the total range of H. johnsonii is actually one clone that is closely related to populations in Africa and Antigua and may be derived from a recent introduction from one of those regions.

Susan Lynn Williams: the Life of an Exceptional Scholar, Leader, and Friend (1951–2018) - William C. Dennison; Matthew E. S. Bracken; Maria Brown; John F. Bruno; James T. Carlton; Robert C. Carpenter; Tim J. B. Carruthers; Megan N. Dethier; Carlos M. Duarte; Thomas R. Fisher; James W. Fourqurean; Richard K. Grosberg; et al. (Estuaries and Coasts, 2021)
Susan Lynn Williams (1951–2018) was an exceptional marine ecologist whose research focused broadly on the ecology of benthic nearshore environments dominated by seagrasses, seaweeds, and coral reefs. She took an empirical approach founded in techniques of physiological ecology. Susan was committed to applying her research results to ocean management through outreach to decision-makers and resource managers. Susan’s career included research throughout the USA in tropical, temperate, and polar regions, but she specialized in tropical marine ecology. Susan’s scholarship, leadership, and friendship touched many people, leading to this multi-authored paper. Susan’s scholarship was multi-faceted, and she excelled in scientific discovery, integration of scientific results, application of science for conservation, and teaching, especially as a mentor to undergraduate and graduate students and postdoctoral scholars. Susan served in a variety of leadership positions throughout her career. She embodied all facets of leadership; leading by example, listening to others, committing to the “long haul,” maintaining trust, and creating a platform for all to shine. Susan was an important role model for women in science. Susan was also a loyal friend, maintaining friendships for many decades. Susan loved cooking and entertaining with friends. This paper provides an overview of the accomplishments of Susan in the broad categories of scholarship, leadership, and friendship.

Seagrass Restoration Is Possible: Insights and Lessons From Australia and New Zealand - Yi Mei Tan; Oliver Dalby; Gary A. Kendrick; John Statton; Elizabeth A. Sinclair; Matthew W. Fraser; Peter I. Macreadie; Chris L. Gillies; Rhys A. Coleman; Michelle Waycott; Kor-jent van Dijk; Adriana Vergés; et al. (Frontiers in Marine Science, 2020)

Review of Coast and Marine Ecosystems in Temperate Australia Demonstrates a Wealth of Ecosystem Services - Sam Gaylard; Michelle Waycott; Paul Lavery (Frontiers in Marine Science, 2020)

Estimating Mangrove Tree Biomass and Carbon Content: A Comparison of Forest Inventory Techniques and Drone Imagery - Alice R. Jones; Ramesh Raja Segaran; Kenneth D. Clarke; Michelle Waycott; William S. H. Goh; Bronwyn M. Gillanders (Frontiers in Marine Science, 2020)

Toward a Coordinated Global Observing System for Seagrasses and Marine Macroalgae - J. Emmett Duffy; Lisandro Benedetti-Cecchi; Joaquin Trinanes; Frank E. Muller-Karger; Rohani Ambo-Rappe; Christoffer Boström; Alejandro H. Buschmann; Jarrett Byrnes; Robert G. Coles; Joel Creed; Leanne C. Cullen-Unsworth; Guillermo Diaz-Pulido; et al. (Frontiers in Marine Science, 2019)

Predicting the cumulative effect of multiple disturbances on seagrass connectivity - Alana Grech; Emmanuel Hanert; Len McKenzie; Michael Rasheed; Christopher Thomas; Samantha Tol; Mingzhu Wang; Michelle Waycott; Jolan Wolter; Rob Coles (Global Change Biology, 2018)
The rate of exchange, or connectivity, among populations effects their ability to recover after disturbance events. However, there is limited information on the extent to which populations are connected or how multiple disturbances affect connectivity, especially in coastal and marine ecosystems. We used network analysis and the outputs of a biophysical model to measure potential functional connectivity and predict the impact of multiple disturbances on seagrasses in the central Great Barrier Reef World Heritage Area (GBRWHA), Australia. The seagrass networks were densely connected, indicating that seagrasses are resilient to the random loss of meadows. Our analysis identified discrete meadows that are important sources of seagrass propagules and that serve as stepping stones connecting various different parts of the network. Several of these meadows were close to urban areas or ports and likely to be at risk from coastal development. Deep water meadows were highly connected to coastal meadows and may function as a refuge, but only for non‐foundation species. We evaluated changes to the structure and functioning of the seagrass networks when one or more discrete meadows were removed due to multiple disturbance events. The scale of disturbance required to disconnect the seagrass networks into two or more components was on average >245 km, about half the length of the metapopulation. The densely connected seagrass meadows of the central GBRWHA are not limited by the supply of propagules; therefore, management should focus on improving environmental conditions that support natural seagrass recruitment and recovery processes. Our study provides a new framework for assessing the impact of global change on the connectivity and persistence of coastal and marine ecosystems. Without this knowledge, management actions, including coastal restoration, may prove unnecessary and be unsuccessful.

Pleistocene sea level fluctuations and the phylogeography of the dugong in Australian waters - David Blair; Adrian McMahon; Brenda McDonald; Daniela Tikel; Michelle Waycott; Helene Marsh (Marine Mammal Science, 2014)
We investigated phylogeography, demography, and population connectivity of the dugong ( Dugong dugon ) in Australian waters using mitochondrial control region DNA sequences from 177 Australian dugongs and 11 from elsewhere. The dugong is widespread in shallow Indo‐West Pacific waters suitable for growth of its main food, seagrass. We hypothesized that the loss of habitat and creation of a land barrier (the Torres Strait landbridge) during low sea level stands associated with Pleistocene glacial cycles have left a persisting genetic signature in the dugong. The landbridge was most recently flooded about 7,000 yr ago. Individual dugongs are capable of traveling long distances, suggesting an alternative hypothesis that there might now be little genetic differentiation across the dugong's Australian range. We demonstrated that Australian dugongs fall into two distinct maternal lineages and exhibit a phylogeographic pattern reflecting Pleistocene sea‐level fluctuations. Within each lineage, genetic structure exists, albeit at large spatial scales. We suggest that these lineages diverged following the last emergence of the Torres Strait landbridge ( ca . 115 kya) and remained geographically separated until after 7 kya when passage through Torres Strait again became possible for marine animals. Evidence for population growth in the widespread lineage, especially after the last glacial maximum, was detected.

Thermal tolerance of two seagrass species at contrasting light levels: Implications for future distribution in the Great Barrier Reef - Catherine J. Collier; Sven Uthicke; Michelle Waycott (Limnology and Oceanography, 2011)
This study assessed metabolism, growth, and survival of two seagrass species at three different seawater temperatures (27°C, 30°C, and 33°C) under saturating (400 µmol photons m ‐2 s ‐1 ) and limiting (40 µmol photons m ‐2 s ‐1 ) light over 1 month. Halodule uninervis grown at 33°C was within its physiological optimum temperature range, exhibiting 2.3× higher photosynthetic rates than at 27°C, and increased net shoot carbon (C) production (up to 10× higher) at saturating light levels. In contrast, 33°C exceeded the optimum temperature threshold for Zostera muelleri , resulting in critical metabolic imbalances with large reductions in photosynthesis and increases in leaf respiration. This led to substantially lower growth rates (0‐2% of those at 27°C) and lower final biomass (only 10% of that at 27°C) in the 33°C treatment after 1 month. This decline at higher temperatures occurred at both light levels, but it was more severe in limiting light, where the C balance went into deficit. H. uninervis in the Great Barrier Reef (GBR) exists well within its optimal temperature range and should continue to thrive at projected future temperatures, at least under saturating light levels. In contrast, Z. muelleri currently exists near its upper thermal threshold, and future temperature increases of the magnitude investigated here would likely lead to the contraction of the range of this species from the northern GBR ‐ potentially by more than 1000 km. This could have ecologically significant ramifications, because Z. muelleri is often the only GBR species that currently inhabits muddy estuarine areas, which are critical fisheries habitats.

Isolation and characterisation of polymorphic microsatellite loci in the vulnerable spectacled flying fox, Pteropus conspicillatus - Samantha Fox; Michelle Waycott; Glenn Dunshea (Conservation Genetics, 2007)

Genetic variation, its assessment and implications to the conservation of seagrasses - MICHELLE WAYCOTT (Molecular Ecology, 1998)
In a study of the widespread Australian endemic seagrass Posidonia australis , allozyme analysis identified a wide range in population genetic structure assessed using the multilocus genotype diversity statistic ( D G ). Values of D G between zero and one were obtained; however, RAPD analysis generally detected higher levels of diversity, where D G values were all greater than 0.5 ( D G = 0.67 – 1). Some populations were allozymically monomorphic using allozyme analysis yet were highly polymorphic using RAPD analysis. The differences observed between methods, particularly among allozymically uniform populations, demonstrate the importance of choosing an appropriate method when assessing genotypic diversity. Different methods may reflect different historical aspects of population processes where allozymes reflect broader‐scale gene flow and population establishment and DNA fingerprinting methods such as RAPDs may reflect fine‐scale local recruitment events and shorter‐term population processes. Using either method alone, particularly in genotypically depauperate organisms such as seagrasses and other clonal organisms, will be problematic in assessing their population genetic potential, a parameter being used by conservation managers to decide upon management strategies in rare and endangered organisms. It is recommended that the impact of disturbance assessed using genotypic diversity measures requires more than one technique to provide the most appropriate information for designing subsequent conservation strategies.